(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article analyzes various methodological strategies and some practices of studying fashion from the standpoint of philosophy and cultural studies. The tendencies to the transformation of the concept of fashion from the phenomenon of consumer culture to the mechanism of identification and the means of expression of the individuality of the subject are revealed. The article deals with the main aspects of the practical existence of fashion in modern times, including the relationship of changes in fashion with the transformation of the basic characteristics of identity. The author explores how the understanding and functioning of fashion changes in the information age. The fashion is shown as a transboundary phenomenon that represents complex identification processes.